The Tree of the Knowledge of Good and Evil: An Attempt to Differentiate Theologems - Theognost, Hieromonk (Bogoslovskie razmyšlenija, 2005)
In the modern world much interest is being shown to religion, its symbols, and its texts. Yet few understand the deep language of Scripture, its deep symbolic semantics. This lack of understanding often becomes the reason why people fall away from the Church (because a surface reading suggests that the Bible speaks in the language of "myth"), or leads to distortion of the realia described in the Bible. What is original sin? What is the tragedy of what Adam did, and why do his descendants suffer for his sin? All of these questions demand a phased explanation for modern people in contemporary, understandable language.This essay, "The Tree of the Knowledge of Good and Evil," discusses one of the fundamental tenets of the Christian religion. It assists in understanding the essence of Adam’s fall. We present to the reader a detailed examination of the way four great Church Fathers—Gregory of Nazianzus, Maxim the Confessor, Gregory of Nyssa, and John Chrysostom—approached the question of interest to us. In the second part of the essay another question is examined: What did the fallen angel actually want of man in Paradise? This theological presentation represents an attempt on the part of the author to examine the question from a fresh, existential perspective